The Use of Accounting Information in Decision Making. - Savich, Richard S. (The Accounting Review, 1977)
Abstract ABSTRACT: Human information processing systems (HIPS) research has progressed to the stage of describing characteristics of decision styles. HIPS also has considered various methodologies to determine modeling techniques of individuals. This paper discusses both the decision style and decision model literature. Subsequently, an experiment which attempts to relate the two fields is conducted. The experiment presents quarterly accounting data and asks subjects to render sell-buy decisions. The decisions are modeled using multiple regression techniques and variables utilized to form the basis for comparison with decision styles. Also perceptions of decision models by subjects was elicited. The results were mixed with respect to decision style comparison but supported modeling perceptions.